2017
DOI: 10.1016/j.seizure.2017.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Real-life experience with brivaracetam in 101 patients with difficult-to-treat epilepsy—A monocenter survey

Abstract: In our hands BRV appeared to be well tolerated and easy to handle. The retention rate was influenced by patients who were switched from LEV and re-switched because BRV was not more efficient. Switching from and re-switching to LEV was easy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
67
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(98 citation statements)
references
References 17 publications
26
67
5
Order By: Relevance
“…In contrast to our results, a recent retrospective study showed a much lower impact on behaviour in adolescents without ID under brivaracetam treatment 15. Patients with BAE on levetiracetam were more likely to develop these on brivaracetam.Our retrospective data do not support the assumption that switching levetiracetam to brivaracetam reduces behavioural changes.…”
contrasting
confidence: 99%
“…In contrast to our results, a recent retrospective study showed a much lower impact on behaviour in adolescents without ID under brivaracetam treatment 15. Patients with BAE on levetiracetam were more likely to develop these on brivaracetam.Our retrospective data do not support the assumption that switching levetiracetam to brivaracetam reduces behavioural changes.…”
contrasting
confidence: 99%
“…These results are in keeping with findings of the three aforementioned retrospective series, [9][10][11] and with those of a meta-analysis, which found BRV, LEV, and gabapentin to have the best tolerability profiles among newer AEDs. These results are in keeping with findings of the three aforementioned retrospective series, [9][10][11] and with those of a meta-analysis, which found BRV, LEV, and gabapentin to have the best tolerability profiles among newer AEDs.…”
Section: Months 6 Months 12 Monthssupporting
confidence: 90%
“…[9][10][11] In two, 101 and 93 patients with focal epilepsy (both 97%), who had failed 10 (median) and 6.3 A sig- These findings are generally consistent with those of other retrospective series.…”
Section: Outcomes Of Patients Who Had Experienced a Stroke (N = 22)supporting
confidence: 87%
“…Retention rates of 82.4% at 3 months and 69.2% at 6 months are comparable with other AEDs licensed for focal epilepsies in the past decade, such as lacosamide (80% at 6 months, 62%‐68% at 1 year), zonisamide (62% at 1 year), PER (60% at 6 months), and eslicarbazepine acetate (80%‐82% at 6 months, 72% at 1 year) . Postmarketing studies of BRV in predominantly focal epilepsies showed comparable retention rates of 51.5%, 72%, and 75.8% at 6 months . In GGE, sufficient data on retention rates are available for LTG, VPA, and LEV; with the highest retention rates for VPA in all GGE subsyndromes (90% at 3 years), followed by LEV (65% at 3 years; only juvenile myoclonic epilepsy) and LTG (45% at 3 years) …”
Section: Discussionsupporting
confidence: 61%
“…In patients who experienced psychobehavioral adverse events while on LEV, starting BRV resulted in psychobehavioral TEASs in five of 30 (17%) patients, whereas this was the case in only four of 31 (13%) patients who did not develop psychobehavioral TEAEs while on LEV or were not exposed to LEV at all. The lower incidence and amelioration of psychobehavioral TEAEs due to switching from LEV to BRV have been shown in one open‐label, prospective, exploratory study and postmarketing publications . The latter showed that the likelihood of psychobehavioral TEAEs was significantly increased in patients who had developed psychobehavioral TEAEs on LEV in the past …”
Section: Discussionmentioning
confidence: 87%